Physicochemical, antioxidant, and polyphenolic attributes of microencapsulated freeze‐dried kinnow peel extract powder using maltodextrin as wall material. Issue 1 (7th December 2021) - Rafiq, Shafiya; Sofi, Sajad Ahmad; Kumar, Harish; Kaul, Raj Kumari; Mehra, Rahul; Awuchi, Chinaza G.; Okpala, Charles Odilichukwu R.; Korzeniowska, Małgorzata
Abstract: The physicochemical, antioxidant, and polyphenolic attributes of microencapsulated freeze‐dried kinnow peel extract powder using maltodextrin as wall material were investigated. The total phenolic, flavonoid, and antioxidant content of fresh peel extract were 24.51 mg GAE/g, 9.12 mg Quercetin/g, and 81.53% scavenging activity, respectively. The maltodextrin prepared from broken rice starch competes well with those commercial types. The microencapsulated kinnow peel powders across feed solutions 10%, 15%, and 20% total soluble solids (TSS) significantly differed ( p < .05)by yield, water absorption, water solubility, swelling capacity, bulk density, antioxidant activity, moisture, water activity, hygroscopicity, water solubility index, swelling capacity, and color. The low cohesiveness and good flowability were respectively demonstrated by Carr index (1.18) and Hausner ratio (15.21) values. The intestinal fluid released more polyphenolic components over the gastric medium. Overall, the maltodextrin as a wall material would effectuate a beneficial microencapsulation process. Practical application: Maltodextrin is among the polysaccharides used as wall materials with desirable characteristics. Despite the previous studies that have evidenced the role of maltodextrin, relevant information about those specifically obtained from broken rice starch for use in the microencapsulation of citrus peel extract is scant. In this work, we demonstrated the maltodextrin specifically obtained from broken rice starch to be a promising wall material for the microencapsulated citrus peel extract powder.